Therapeutic effect of Yoga in the management of Hypertension: A case series - Narathota, S.N.L.; Wimalasiri, Y.S.G. (University of Colombo, 2025)
Yoga is a multifaceted spiritual discipline that promotes health and well-being by the union of body, mind and soul. Its components commonly applied for therapeutic benefits include Asanas (physical postures), Praṇayama (regulated breathing), and meditation. Hypertension is a major risk factor for coronary artery disease and cerebrovascular accidents. Yoga holds a notable place in the nonpharmacological management of Hypertension. An observational study was conducted for one month at the Yoga clinic of Rural Ayurveda Hospital, Kesbewa, to evaluate the therapeutic effect of selected Yoga practices on reducing systolic and diastolic blood pressure in female patients with chronic hypertension undergoing conventional antihypertensive treatment. After obtaining consent, ten female patients aged between 45 and 55 years with chronic Hypertension on medication, and without any joint disorders, were selected. In the study, Sukhasana (Easy Pose), Nadishadhana-Praṇayama (breathing exercises) and Shavasana (Corpse Pose) were utilized. The methods of practicing the above-mentioned Asanas were demonstrated, and the patients were advised to practice them in morning from 9-10 am for 01 hour, spending 20 minutes on each Asana, and to attend the clinic every Saturday for 04 weeks for clinical examination and blood pressure (BP) monitoring. BP readings were recorded before and after the intervention. The results showed a reduction in both systolic and diastolic BP across all participants. The mean BP before the intervention was 140/90 mmHg, which decreased to 130/80 mmHg following the 01-month Yoga regimen. These findings suggest that Yoga may offer a beneficial adjunct to conventional Hypertension management. Further studies with a larger sample size and controlled conditions, such as participants practicing Yoga without concurrent Antihypertensive medications can be recommended to strengthen the evidence base.
Keywords: Dushta vrana; Vrana shodhana; Krimighna; Kaphashamana